Estresse Ocupacional, qualidade do sono e obesidade em Policiais Militares - Revisão narrativa (Research, Society and Development, 2021)
Stress was considered by the United Nations as the disease of the 20th Century, being present in more than 90% of the world population, including military police officers. This group of professionals has been in the front-line of the pandemic caused by the Coronavirus and is exposed to daily situations of high emotional stress and traumatic work events, which can cause several health problems, namely occupational stress, sleep problems and obesity. This study aims to conduct a narrative review of the influence of psychosocial environment on the development of occupational stress and consequences on the military police officer´s health. Two platforms, namely PubMed and Google Scholar were used to search for relevant scientific publications on the topic; 148 publications from 2010 to 2020 were analyzed, 71 of which were included in this review. It is estimated that 25% to 35% of the global burden of disease may be due to environmental factors. The stress prevalence in military police officers is higher than the average in the civilian population worldwide; due to an alternate work schedule that does not always respect the circadian characteristics of each individual, and with direct influence on sleep quality and obesity incidence. Public health policies should be taken in the short term in order to improve life quality of these professionals.